Unveiling the mechanisms of American ginseng and achyranthes in treatment of primary Sjogren’s syndrome via mtDNA-cGAS-STING pathway insights from network pharmacology, molecular dynamics, and experimental validation - Li, Haotian; Xia, Congmin; Song, Yuewei; Chen, Jin; Liu, Yanjun (Frontiers in Immunology, 2025)
ObjectiveWith the aim of clarifying the therapeutic mechanisms of the American Ginseng-Achyranthes bidentata (AG&A) herbal pair in primary Sjögren’s syndrome (pSS), this study employs an integrated approach combining network pharmacology, molecular docking, molecular dynamics simulations, and animal experiments.MethodsNetwork pharmacology & LC-MS/MS was utilized to identify the active components and potential targets of A&A. Molecular docking and dynamics simulations were performed to evaluate binding affinity and complex stability with key targets. Animal experiments using non-obese diabetic (NOD) mice were conducted to validate symptom improvement by critical active components.ResultsNetwork pharmacology identified baicalin and quercetin as key active components. Molecular docking revealed strong binding affinities (binding energy ≤ -8.0 kcal/mol) between these compounds and apoptosis-related proteins, BAX and CASP3. Molecular dynamics simulations confirmed the stability of these complexes. Animal experiments demonstrated that baicalin can significantly reduce inflammatory cytokines of IL-18, TNF-α, IFN-α, and IFN-β,CXCL-10 (p < 0.05), decrease mtDNA release, and downregulate cGAS-STING pathway-related proteins including cGAS, STING, CASP3, ZBP1, TBK1, p-STING, p-TBK1, IRF3, p-IRF3 and BAX.ConclusionThe critical components baicalin and quercetin from AG&A, particularly in aqueous extracts, exhibit therapeutic efficacy against pSS. This study provides experimental evidence for their action mechanism through modulating the mtDNA-cGAS-STING pathway. While highlighting their therapeutic potential, additional in vivo and clinical studies are warranted to validate these findings.